Expert review on soft-tissue plasmacytomas in multiple myeloma: definition, disease assessment and treatment considerations - Rosinol, Laura; Beksac, Meral; Zamagni, Elena; Van De Donk, Niels W. C. J.; Anderson, Kenneth C.; Badros, Ashraf; Caers, Jo; Cavo, Michele; Dimopoulos, Meletios-Athanasios; Dispenzieri, Angela; Einsele, Hermann; Engelhardt, Monika; et al. (British Journal of Haematology, 2021)
In this review, two types of soft-tissue involvement in multiple myeloma are defined: (i) extramedullary (EMD) with haematogenous spread involving only soft tissues and (ii) paraskeletal (PS) with tumour masses arising from skeletal lesions. The incidence of EMD and PS plasmacytomas at diagnosis ranges from 1·7% to 4·5% and 7% to 34·4% respectively. EMD disease is often associated with high-risk cytogenetics, resistance to therapy and worse prognosis than in PS involvement. In patients with PS involvement a proteasome inhibitor-based regimen may be the best option followed by autologous stem cell transplantation (ASCT) in transplant eligible patients. In patients with EMD disease who are not eligible for ASCT, a proteasome inhibitor-based regimen such as lenalidomide-bortezomib-dexamethasone (RVD) may be the best option, while for those eligible for high-dose therapy a myeloma/lymphoma-like regimen such as bortezomib, thalidomide and dexamethasone (VTD)-RVD/cisplatin, doxorubicin, cyclophosphamide and etoposide (PACE) followed by SCT should be considered. In both EMD and PS disease at relapse many strategies have been tried, but this remains a high-unmet need population.
CRIS-Team Scopus Importer:2023-03-23
Keywords: extramedullary disease; multiple myeloma; paraskeletal plasmacytomas; plasmacytoma; prognosis; soft tissue; treatment